Chemical composition, physical properties, and immunomodulating study of mare's milk of the Adaev horse breed from Kazakhstan - Kossaliyeva, Gaukhar; Rysbekuly, Kaster; Zhaparkulova, Karlygash; Kozykan, Sabira; Li, Juxiu; Serikbayeva, Assiya; Shynykul, Zhanserik; Zhaparkulova, Maira; Yessimsiitova, Zura (Frontiers in Nutrition, 2025)
Mare's milk is recognized for its nutritional and immunomodulatory properties, making it a promising functional food. Furthermore, mare's milk is characterized by anti-carcinogenic and antiviral attributes, which have incited considerable scientific inquiry. This study investigates the chemical composition, immune-modulating effects, and physiological impact of Adaev horse milk supplementation in a Streptococcus pneumoniae-infected Wistar rat model. Eighteen male rats were divided into three groups: a control group (GC-1) receiving standard chow, a low-dose supplementation group (LDM-2) receiving 0.1 g of lyophilized mare's milk, and a high-dose group (HDM-3) receiving 1.5 g of lyophilized mare's milk. SDS-PAGE analysis revealed that Adaev horse milk is rich in whey proteins and has lower casein content, enhancing protein digestibility and bioavailability. HILIC-MS identified key sialylated oligosaccharides [lactose, 3′-sialyllactose (3′SL), 6′-sialyllactose (6′SL), 3′-α-sialyl-N-acetyllactosamine (3′SLN), sialyllacto-N-tetraose a (LSTa), sialyllacto-N-tetraose b (LSTb), and sialyllacto-N-tetraose c (LSTc)], suggesting potential prebiotic and immunomodulatory effects. Blood serum analysis demonstrated increased total protein levels in supplemented groups, with significant alterations in albumin/globulin ratios, creatinine, and enzyme activity. Histological examination of lung tissues indicated that high-dose supplementation reduced inflammatory damage, improved tissue integrity, and enhanced immune recovery. These findings suggest that Adaev horse milk supplementation modulates immune responses, improves metabolic and hematological parameters, and mitigates pneumonia-induced tissue damage, highlighting its potential as a functional dietary supplement with immunotherapeutic benefits.